Existing Technology of Beef Cattle on Farmer Group of Lembu Agung, District Kurik, Merauke Regency - Tiro, Batseba M.W. (Faculty of Agriculture, Janabadra University, 2017)
This study aims to determine existing technology in cultivation of beef cattle in farmer group of Lembu Agung. Secondary data collected cover potential of area and livestock population, while primary data include number of livestock, maintenance system, feed management and reproduction performance. Data collected through Foccus Group Discussion (FGD) method using a semi-structured questionnaire. Results of study showed that farmer group of Lembu Agung had 24 cows, consisting of 17 adult cows, 4 adult bulls Â and 3 calves, with a relatively low maintenance scale of 1-2 head. Maintenance system is still semi-intensive with minimal management especially in terms of providing adequate feeding throughout year. Feeding only rely on availability of natural grass and a small part of elephant grass planted in rice field area, with amount of green forage is only about 5-10 kg/head/day. Reproduction performance of parent with existing technology includes calving rate (60%); Body condition score (BCS) of cow (2-2,5); Calving interval (18-24 months); Birth weight (15-18) and calf crop (40-50%). This study shows that feed problems are a limiting factor in cattle farming although potential for feed is sufficiently available but not yet optimally utilized, this has an impact on low productivity of cattle.Â Key-words: Behavior, technology, beef cattle